"O Éden desejado e querido": história, fotografia e educação no Espírito Santo durante a Primeira República (1908-1912) - Costa, Cíntia Moreira da (2016)
The present research proposes a reading of the photographic records referring to the school universe present in the documents produced by the Government of the State of Espírito Santo during the administration of Jeronymo de Souza Monteiro in the years 1908-1912. The photographs inserted in the government’s final address to the Legislative Congress, entitled “Statement about the state businesses during the years 1908-1912 by his Excellency Dr. Jeronymo Monteiro, president of the state in the same period” form the documental corpus of this work. The research intends to identify how the implementation of the republican educational project in the State of Espírito Santo took place during the First Republic, particularly in Jeronymo Monteiro’s government - a project that was strongly inspired by the pedagogical and administrative reform model in the educational field launched in the State of São Paulo in the previous decade. In compliance with an ideology of progress based on the principles of positivism and of liberalism which supported republican discourse, public education was considered a strategic area in order to overcome the economic lag in which the State of Espírito Santo was. By means of images, we sought to verify how the educational institutions reproduced the prevailing inequalities of society. If at some times they subsidize verbal speech, at others, images go against it, thus bringing information which is diverse from that conveyed through words. The present work assumes that photography is not essentially an impartial document; much on the contrary: it presupposes the establishment of a dialectic and dialogic process between “reality”, the photographer and the reader.